A Decade of Researching on Professional Development in a Graduate Program: A Systematic Review - Le, Thanh Thao; Le, Xuan Mai (FOSTER: Journal of English Language Teaching, 2022)
This paper aims to provide a logical and comprehensive systematic review of MA students’ theses related to professional development (PD) in an educational institution in the Mekong Delta of Vietnam. This systematic review used a qualitative method to analyze 28 unpublished PD theses (2010 – 2020) in a graduate program of a public tertiary institution in the Mekong Delta, Vietnam. There were four main research concerns, including (1) research aims, (2) research methodology, (3) findings, and (4) limitations of the theses. After the review, a list of strengths and weaknesses of these studies is found, evaluated, and presented in this article. The review shows that these studies did contribute diverse knowledge and practices of PD in the educational system of Vietnam, particularly in the Mekong Delta. On the other hand, the data collection instruments and research designs needed improvement to a certain extent. Specifically, observations were not used much in the theses. Besides, the candidate researchers overused a descriptive research design for their theses. Thanks to the analysis, some implications and new ideas for further research in PD are discussed at the end of this paper. .